Comparative Evaluation of Problem-Based Learning and Traditional Teaching Methods in Enhancing Preventive Health Strategies Among Medical Students - Shagufta Haider, Muhammad Azhar Khan, Qaiser Masud Sheikh, Jamshad Ahmed, Ahsan Qureshi, Abdul Wadood Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Preventive health is a critical component of medical education, requiring both theoretical knowledge and applied skills. While lecture-based learning (LBL) remains the traditional teaching method, problem-based learning (PBL) has been proposed as a more interactive and student-centered approach. Evidence comparing these methods in preventive medicine remains limited, particularly in Pakistan. Objective: To compare the effectiveness of problem-based learning and lecture-based learning in teaching preventive health strategies among undergraduate medical students. Methods: A quasi-experimental study was conducted at Gambat Medical College, Gambat, and Women Medical College, Abbottabad, from January 2022 to May 2023. A total of 150 third-year MBBS students were enrolled, with 75 allocated to PBL and 75 to LBL. Both groups covered identical content on six core areas of preventive medicine. Outcomes measured included performance in a four-station Objective Structured Clinical Examination (OSCE), a 50-item knowledge test, a self-efficacy scale for preventive counseling, an attitude scale, and student satisfaction. Data were analyzed using SPSS version 26.0, with independent t-tests and chi-square tests applied where appropriate. Results: Students in the PBL group achieved significantly higher composite OSCE scores compared with the LBL group (82.6 ± 7.4 vs. 76.8 ± 8.1; p < 0.001). Station-wise analysis revealed superior performance in all four stations, particularly in tobacco cessation counseling. Knowledge scores were higher in the PBL group (38.9 ± 4.6) than in the LBL group (36.2 ± 5.1; p = 0.001). Self-efficacy was also significantly greater (4.2 ± 0.5 vs. 3.7 ± 0.6; p < 0.001), as were attitudes toward preventive medicine (4.0 ± 0.4 vs. 3.7 ± 0.5; p = 0.002). Satisfaction was higher among PBL students, with 84% rating the method highly satisfactory compared with 62% in the LBL group (p = 0.004). Conclusion: Problem-based learning was found to be more effective than lecture-based teaching in enhancing preventive health education among medical students. PBL improved applied performance, knowledge retention, self-efficacy, attitudes toward prevention, and overall satisfaction. These findings support the integration of PBL into medical curricula for effective training in preventive health strategies. Keywords: Problem-Based Learning, Lecture-Based Learning, Preventive Medicine, Medical Education, OSCE, Self-Efficacy, Attitudes